Childbirth Research : New Developments. - Kelly, Ginger M. (Obstetrics and gynecology advances., 2012)
In this book, the authors present new developments in childbirth research. Topics discussed in this compilation include the theoretical and research findings on the psychopathology during transition to parenthood as a critical life event; the voices of postnatal women and how their experiences enhance antenatal practice; a sociological understanding of women's childbirth discourses; ethical analysis on therapeutic abortion for fetal abnormality; the use of placental blood in term and pre-term newborns; self-efficacy theory and intervention in childbirth; and anal sphincter damages in childbirt.